Kajian Tanah Menurut Pedologi dan Etnopedologi pada Usahatani Padi Ladang di Kecamatan Kulisusu Kabupaten Buton Utara - Miska, Miska; Hemon, M Tufaila; Alam, Syamsu; Zulfikar, Zulfikar; Syaf, Hasbullah; Rustam, La Ode (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Pedology is a science that studies the origin or relationship between soil and soil formation factors and characteristics, while Ethnopedology aims to document and understand local approaches to the perception, classification, assessment, use and management of land. Soil has characteristics that influence the growth of plants that will be cultivated. This research aims to examine soil according to pedology and document ethnopedological studies on field rice farming in Kulisusu District in North Buton Regency. This research was carried out in Kulisusu District, North Buton Regency from November 2023 to April 2024. The method used in this research was a free survey method to characterize the land planted with rice fields. Apart from that, structured interviews were also conducted with each rice field manager. There are 3 soil sampling locations, namely Tomoahi, Eelahaji and Jampaka Villages, each with a different soil color. The samples taken are analyzed in the laboratory, namely soil texture. Research for the Kulisusu community's knowledge of soil color in rice fields, namely profile I in layer I (10 YR 5/8, Yellowish Brown), layer II (10 YR 4/6, Dark Yellowish Brown), layer III (10 YR 6 /8, Brownish Yellow), in profile II in layer I (10 YR 3/4, Dark Yellowish Brown), layer II (10 YR 5/4, Yellowish Brown), layer III (2.5 Y 8/4, Pale Yollow), while profile III is in layer I (10 YR 3/2, Very Dark Grayish Brown), layer II (10 YR 4/3, Brown). Soil texture in paddy fields, namely profile I in layer I (clay textured), layer II (dusty clay texture), layer III (clay textured), in profile II layer I (clay textured), layer II (clay textured), layer III (clayey clay texture), and profile III for layer I (clayey clay textured), and layer II (clayy clay textured). The soil structure in each land profile has a uniform shape and size, namely rounded cubes and medium coarse size. The results of research carried out in the field show that the results are almost uniform, namely that micro pores have large and small results.